PENERAPAN STRATEGI PEMBELAJARAN EVERY ONE IS A TEACHER HERE BERBANTUKAN LEAFLET BERMUATAN NILAI-NILAI KARAKTER DALAM PENCAPAIAN KOMPETENSI FISIKA SISWA KELAS X SMAN 5 PADANG - Rihyo Riski Putra (PILLAR OF PHYSICS EDUCATION, 2014)
The problem of learning in this research is learning every one is a teacher here with leaflets charged values character in the attainment of competence students. The purpose to be achieved is to know the influence of the implementation of a strategy of learning every one is a teacher here with leaflets charged values character in the attainment of competence physics students grade X SMAN 5 Padang. Methods used in this research are experiment methods of this research is  quasi experiment with randomized control group only design. Population in this research is all students grade X in SMA 5 Padang that registered in the academic year 2013 / 2014. The technique of sampling is cluster random sampling. The samples to this research is two classes X, class X 1 as a class experimentation and class X 7 as a control class.The research data include the achievement of competence in two aspects, the cognitive and affective aspects. Engineering assessment was done by using a test for non-technical aspects of cognitive and affective aspects of the test for. The data obtained were analyzed using two test average similarity with the real level of 0.05. Based on test data that has been done, it can be concluded that the application of learning strategies every one is a teacher here with leaflets charged character values in the achievement of competence Physics class X student of SMAN 5 Padang, affects the results of physics students' learning competence